Clinical social work's contribution to a social justice perspective - Swenson, Carol R. (1998)
Social justice is increasingly described as the organizing value of social work. But does that apply to clinical social work? Following Wakefield, this article argues that it does and offers a variety of theories and practices to elaborate this claim, including ways to understand clients in the contexts of their strengths, social positions, and power relationships. In addition, clinicians can develop techniques to enable clients to understand themselves in these relationships and to be liberated when these relationships are oppressive. The clinician engages in self-reflection about personal experiences, not only of oppression but also of privilege and domination. Clinicians may work with people who are privileged and powerful to help them assess their motivation to change behavior associated with such roles. And finally, clinicians can develop new structures in agencies to counter oppressive beliefs and practices and work to develop programs that will offer social, economic spiritual, political, and psychological resources. Social workers can offer a social justice perspective to members of other therapeutic professions who are interested in clinical social justice practice. - Reproduced
Keywords: Social work; Social justice